Faktor-Faktor Pengaruh Prokrastinasi pada Siswa atau Siswi MA Patra Mandiri - Rizki Amaliyah; Muhammad Ramanda Sukma (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Procrastination is not only a wall that prevents students from achieving academic achievement, but is also detrimental to the psychological well-being and personal development of students and students. Several factors that pay attention to the attitudes of each student can cause stress, indifference to learning, and inability to achieve educational targets. Therefore, the aim of the research project is to determine the factors of procrastination that influence male and female students. In this research, qualitative methods were chosen, and data was obtained through interviews and observation. Finally, we arrived at the conclusion that academic pressure and social pressure, time problems and motivation management are procrastination factors that influence MA Patra Mandiri students and students